A lightweight visualization tool for protein unfolding by collision detection and elimination - Qian, Hua; Chen, Yu; Jiang, Yelu (Frontiers in Computer Science, 2024)
The experiments involving protein denaturation and refolding serve as the foundation for predicting the three-dimensional spatial structures of proteins based on their amino acid sequences. Predicting protein structures directly from protein sequences is highly valuable for exploring the relationship between protein structure and function, driving advancements in protein engineering and design. In theory, protein sequences encode information about the spatial arrangement of the folded protein, suggesting the potential to deduce the native folded protein structure from the amino acid sequence alone. Despite significant progress in protein structure engineering, exemplified by AlphaFold2, OmegaFold, FoldingDiff and ForceGen, there remains a gap in understanding the folding pathways of polypeptide chains leading to their final structures.We developed a lightweight tool for protein unfolding visualization called PUV whose graphics design is mainly implemented by OpenGL. PUV leverages principles from molecular biology and physics, and achieves rapid visual simulations of protein polypeptide chain unfolding through mechanical force and atom-level collision detection. This methodology can provide essential support for investigating protein folding mechanisms and pathways.